Acute myocarditis with preserved ejection fraction: the role of CMR in long term follow up. (14th October 2021) - Ghionzoli, N; Mandoli, G E; Gismondi, A; Di Florio, A; Cavigli, L; Sciaccaluga, C; Pastore, M C; D'Ascenzi, F; Cameli, M; Focardi, M
Abstract: Background: Cardiac Magnetic Resonance (CMR) has an important role in subjects presenting with acute myocarditis and preserved ejection fraction (pEF); it is widely used as a non-invasive imaging test in patients with suspected myocarditis, both for diagnostic and prognostic purpose. Despite this, poor data is available regarding which parameters define a worst prognosis in acute myocarditis with pEF. Purpose: The aim of this study was to analyze the role of CMR in acute myocarditis with pEF at long term follow up. Methods: We retrospectively enrolled 61 patients admitted to our Cardiology Department with suspected acute myocarditis and pEF. In the acute phase we analyzed clinical parameters, blood sample tests, echocardiographic and CMR indices. Myocarditis was confirmed using the Lake-Louis criteria on CMR images. The patients were followed up for a median of 4.8 years for the development of two composite endpoints: the first including cardiovascular death, cardiac arrest and/or ICD implantation; the second hospitalization for acute heart failure and/or recurrence of myocarditis. Results: The clinical presentation was infart-like in the 78% of subjects; they all had a NYHA class I and had a pEF at basal echocardiogram. CMR showed myocardial edema in 50 patients (83%) and late gadolinium enhancement (LGE) in 94% of subjects. LGE involved the inferolateral wall in the 70%, the interventricular septum in 25% and other walls in 5%. During follow up, the first composite endpoint occurred in the 8% of patients, while 7 subjects (11%) had a new hospitalization for cardiac causes (heart failure or recurrence of myocarditis). Those patients with events during follow up had a significantly higher LGE quantity (21±9, 8 gr vs 12, 8±6 gr; p=0.006 Figure 1) at basal CMR compared to the other group. Conclusions: LGE quantification by CMR could represent a prognostic added tool at long-term follow up in patients presenting with acute myocarditis and left ventricular pEF. Funding Acknowledgement: Type of funding sources: None.